Enhancing panic disorder treatment with mobile-aided case management: an exploratory study based on a 3-year cohort analysis - Tsai, Chan-hen; Christian, Mesakh; Lai, Feipei (Frontiers in Psychiatry, 2023)
Background Individuals with panic disorder frequently face ongoing symptoms, suboptimal treatment adherence, and increased relapse rates. Although mobile health interventions have shown promise in improving treatment outcomes for numerous mental health conditions, their effectiveness, specifically for panic disorder, has yet to be determined. Objective This study investigates the effects of a mobile-aided case management program on symptom reduction and quality of care among individuals with panic disorder. Methods This 3-year cohort study enrolled 138 participants diagnosed with panic disorder. One hundred and eight participants joined the mobile-aided case management group and 30 in the treatment-as-usual group. Data were collected at baseline, 3-month, 6-month, and 12-month treatment checkpoints using self-report questionnaires, in-depth interviews, direct observation, and medical record analysis. Results During the maintenance treatment phase, the mobile-assisted case management group decreased both panic severity (p = 0.008) and state anxiety (p = 0.016) more than the control group at 6 months. Participants who underwent case management experienced enhanced control over panic symptoms, heightened self-awareness, and elevated interpersonal support. Conclusion The mobile-aided case management is beneficial in managing panic disorder, especially maintenance treatment.